Enhancing Reporting Quality through Systems, Controls, and Efficiency - Prasetianingrum, Septyana; Siti Mariani Basannang; Adriani Lande; Yaya Sonjaya; Matelda Samori (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2026)
This study examines the role of accounting information systems (AIS) and internal control systems (ICS) in improving the quality of financial reporting (QFR), with the efficiency of accounting processes (EAP) serving as a mediating variable. Data were collected from 73 employees of the Regional Financial and Asset Management Agency (BPKAD) of Makassar City and analyzed using structural equation modeling. The results indicate that both AIS and ICS have a significant direct effect on QFR, with ICS exerting a more substantial influence. EAP was also found to significantly improve reporting quality and serve as a mediator between AIS, ICS, and QFR. The findings extend Decision Usefulness, Stewardship, and Institutional theories by demonstrating that reporting quality arises from the interaction of systems, controls, and efficiency. Practically, the study highlights the need for governments to align technology, control frameworks, and process efficiency to strengthen financial accountability.